68Ga-DOTATATE and 68Ga-PSMA Uptake in Granulomatous Prostatitis. (10th April 2022) - Ruan, Dan; Sun, Long
Abstract: 68 Ga-PSMA and 68 Ga-DOTATATE PET/CT have shown promising performance in diagnosing prostate cancer and neuroendocrine tumors, but there are also pitfalls. We report a case of a 78-year-old man with prostate lesions showing intense uptake of 18 FDG, 68 Ga-PSMA, and 68 Ga-DOTATATE simultaneously, with heterogeneous enhancement on contrast-enhanced CT and abnormal signal changes on PET/MRI. It was finally diagnosed as granulomatous prostatitis. This case suggests that granulomatous prostatitis has a high uptake of various imaging agents and is easily misdiagnosed as prostate cancer.